Correlation between MET protein expression and MET gene copy number in a Caucasian cohort of non-small cell lung cancers according to the new IASLC/ATS/ERS classification. Issue 4 (June 2015) - Weingertner, Noëlle; Meyer, Nicolas; Voegeli, Anne-Claire; Guenot, Dominique; Renaud, Stéphane; Massard, Gilbert; Falcoz, Pierre-Emmanuel; Olland, Anne; Mennecier, Bertrand; Gaub, Marie-Pierre; Lindner, Véronique; Ghnassia, Jean-Pierre; et al.
Abstract : Summary: MET pathway is a promising target in non-small cell lung cancers (NSCLC) requiring companion tests. The aim of this study was to compare MET expression/gene copy number in a Caucasian population of NSCLC patients. We analysed 201 NSCLC, with 141 adenocarcinomas classified according to 2011 IASLC recommendations, for MET expression by immunohistochemistry (IHC) and gene copy number (GCN) by silver in situ hybridisation (SISH) on tissue microarrays. Mutations in EGFR, KRAS, BRAF, HER2, PIK3CA genes and ALK rearrangements were determined. MET overexpression was observed in 44% and a high MET GCN (≥5 copies) in 14%. MET CGN was correlated with MET expression, regardless of IHC scores ( p  < 0.001) but only 31% of MET overexpressed cases were SISH positive. MET overexpression/GCN number was more frequent in ADC than the other types ( p  < 0.001), the highest in high grade (74%/34%) and sarcomatoid ADC (86%/43%). Mutations of current genes or ALK rearrangements were identified in overexpressed or amplified MET cases. MET overexpression was an independent prognostic factor for overall survival in non-smoker NSCLC in univariate ( p  = 0.01) and multivariate ( p  = 0.01) analyses. MET overexpression is more frequent than MET high GCN, particularly in high grade ADC, regardless of EGFR, KRAS, BRAF, HER2, PIK3CA and ALK status in NSCLC. Abstract : Supplemental Digital Content is available in the text